Technical stakeholders' perspective of solar photovoltaic system failure in Sub-Saharan Africa: The case of Ghana - Owusu, Jacob Junior; Okoroigwe, Edmund C.; Mgbemene, Chigbo A.; Takyi, Gabriel; Ekechukwu, Onyemaechi Valentine (Sustinere: Journal of Environment and Sustainability, 2025)
In many parts of sub-Saharan Africa, grid-connected electricity is unreliable and frequently unavailable in rural locations. Alternative electricity-generation fossil-fuel sources are prohibitive. Solar energy photovoltaic systems have great potential in bridging the energy gap in electricity off-grid locations in sub-Saharan Africa and contribute to the region’s energy portfolio at utility and/or domestic levels. Most installed PV systems in sub-Saharan Africa have often not achieved their anticipated functionality and/or fail frequently. Take-up of PV systems consequently remains low, with long pay-back times. In this study, we have investigated the barriers and challenges associated with PV system operation and probable causes of failure of installed systems within the sub-Saharan Africa region from the perspective of technical stakeholders. We undertook a broad consultation of technicians (installers), engineers, project supervisors, and other technical stakeholders via questionnaires and interviews in a typical sub-Saharan African setting, namely Ghana. Our results show that component quality, cost, availability, and customer preferences are dominant factors considered by the technical stakeholders in component selection during the planning and execution of PV projects. The survey analysis revealed that inverters and batteries are components that account for the most malfunctioning and failures in installed PV systems, while PV panels account for the least. Low product quality, user errors, natural/environmental incidents, and poor sizing/installation errors are identified as key causes of components’ failure.